Perceived in-group discrimination by first and second generation immigrants from different countries of origin in 27 EU member-states. (January 2017) - André, Stéfanie; Dronkers, Jaap
This article analyses perceived in-group discrimination of 29, 189 first and second generation immigrant respondents from 201 different countries of origin currently living in one of 27 EU countries. In addition to testing effects of individual factors, the article estimates the effects of macro-characteristics of both origin and destination countries and community variables. The migration history of these groups is relevant for perceived discrimination: immigrants with citizenship, who speak the majority language at home and have at least one native parent perceive less in-group discrimination, whereas religious respondents, especially from religions that differ more in comparison to the majority, perceive more in-group discrimination. Furthermore, macro-characteristics of the country of origin are most important in explaining differences between European countries. Immigrants from socio-economically more developed countries with higher living standards – and for that reason more comparable to the native population – are less likely to perceive in-group discrimination.